Chemical and microbiological characterization of a technological variant of Vitafert intended for animal production. Technical note - Bustamante, D.; Savón, Lourdes; Elías, A.; Caro, Y.; Valiño, Elaine; Valera, M.; Martin, C.; Mireles, S. (Cuban Journal of Agricultural Science, 2021)
To chemically and microbiologically characterize a technological variant of Vitafert, intended for animal production, chemical composition and amino acid profile of dry Vitafert were determined. In the microbiological analysis, populations of lactic acid bacteria, yeasts, fungi and pathogenic microorganisms were evaluated. A descriptive analysis was applied for data processing. Glutamic acid, leucine, proline, aspartic acid and alanine were predominant in the amino acid pattern. Dry Vitafert showed high concentration of lactic acid bacteria (15 x 107 CFU.g-1) and absence of pathogenic microorganisms. Concentration of individual short chain fatty acids was low and the pH value was 5.41. Results indicate the potential of dry Vitafert for its use in animal feed, due to its chemical composition and concentration of lactic acid bacteria. Keywords: fermented product, chemical composition, microbial populations, feeding